Sexual function in adolescents and young adults (AYA) with Bladder exstrophy-epispadias complex: Influence of the incontinence - Lara Merino-Mateo; Daniel Cabezalí Barbancho; Cristina Tordable Ojeda; Andrés Gómez Fraile (Journal of Pediatric Surgery Open, 2024)
Background: Bladder exstrophy-epispadias complex (BEEC) is the most severe congenital anomaly involving the urinary tract. Currently, there is a growing interest in the long-term outcomes and their impact on quality of life (QoL). Methods: Our aim was to determine the incidence of urinary incontinence and whether it affects sexual function. The study population included BEEC patients >18 years treated at a specialized third-level hospital. We contacted them via telephone and emailed a voluntary online questionnaire which was anonymously self-completed. The online test included validated questionnaires to assess the following parameters: incontinence (ICIQ-SF), LUTS (ICIQ-FLUTS/IPSS) and sexual function (FSH/FSM2). Answers of the questionnaires were collected into a database for further evaluation. Statistical significance was defined by p < .05. Results: Among the thirteen patients (7 men and 6 women) who answered the questionnaire the median score on ICIQ-SF was 6/21. Based on that questionnaire only 4 patients (30.8 %) were classified as continent (ICIQ-SF = 0). However, when directly asked if they were able to stay dry in their day-to-day life, 61.5 % responded affirmatively, a number that doubled those who were considered continent according to the ICIQ-SF test. Incontinence was associated with an increased sexual dysfunction, having a correlation with low satisfaction in men and diminished libido and lubrication in women. Conclusions: In the present study, we found a high incontinence rate, which is discrepant with the self-perception of day-to-day dryness. In addition, our data showed that incontinence is linked to a diminished sexual function.